Implementasi Low Power Mode Pada Sistem Pemberi Pakan dan Minum Pada Ternak Ayam Potong Berdasarkan Waktu Berbasis Arduinomega 2560 - Rahmat Yanuar Putra; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In chicken farming one of the things that needs to be considered is the process of feeding and drinking so that the chicken has good meat quality for public consumption as well as nutritious feeding. Because it is necessary to design tools that can feed and drink automatically, in feeding and drinking is done at the same time as drinking is carried out at a certain time based on a Real Time Clock that can pass the time under real conditions. At the valve the place to eat and drink is given an actuator sensor as a driving force, when the condition of the container starts a little will be notified by the buzzer. This tool can also be Save power with Low Power